Deterioration of insulin sensitivity and beta-cell function in overweight Hispanic children during pubertal transition: A longitudinal assessment - GORAN, MICHAEL I. (2006)
PURPOSE: To examine 1-year changes in insulin dynamics in overweight Hispanic children at high-risk of type 2 diabetes as a function of body composition and pubertal transition. EXPERIMENTAL DESIGN: Longitudinal changes in insulin dynamics, body composition and maturation were determined in 132 Hispanic children (70 boys/62 girls; aged 10.9±1.8 years). METHODS: Body composition was determined by dual energy x-ray absorptiometry and Tanner stage by physical examination. Insulin sensitivity (SI), the acute insulin response to glucose (AIR) and the disposition index (DI; an index of beta-cell function) were determined using an insulin modified intravenous glucose tolerance test. These measures were conducted at baseline and 1-year later. RESULTS: Fat mass increased by 13% (3.0 kg) and SI declined by 24%. In repeated measures analysis of variance, the fall in insulin sensitivity over 1 year remained highly significant even after adjusting for baseline fat mass, age, gender and change in fat mass. The fall in SI was not significantly influenced by Tanner stage. However, subjects in earlier maturation showed a compensatory increase in AIR (i.e. appropriate beta-cell compensation), whereas subjects in the latter stages of maturation did not (i.e. poor compensation). CONCLUSIONS: These results indicate that failure to increase AIR in response to the fall in SI may be one factor in the pathogenesis of the progression of pediatric type 2 diabetes in this at risk population.